The Strength of Deed of Consent Roya as Substitute for Lost Certificate of Mortgage Rights in Demak District - Aini, Maghfiroh; Hasana, Dahniarti (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
The purpose of the research is to find out and analyze the implementation of making a Consent Roya deed as a substitute for a lost mortgage certificate and to analyze and examine the legal position and strength of the Consent Roya deed as a substitute for a lost mortgage certificate in the process of roya mortgage rights. The approach used in this research is Juridical Sociological, the juridical sociological approach technique is used to analyze and provide answers about legal issues in accordance with the intended target. The results of this study are the registration process and the completeness of the files related to the roya application using the roya consents deed is the same as the general roya service. The roya license deed or roya consents of mortgage rights have the same content and purpose, only different mentions based on the habits of each notary. The loss of the mortgage rights certificate results in the royalties not being able to be carried out. Land certificates that are still charged with mortgage rights cannot be resold or other legal actions if they have not been completed. Therefore, to replace the lost SHT, the BPN office requires to attach a Roya Consent Deed in the form of a notarial authentic deed. The roya permit deed made by a notary, its position is only as a substitute for the lost mortgage certificate in the roya process not for execution, so its position cannot be equated with a mortgage certificate that has executive power because it is not regulated in law or strict rules. The Roya license deed is a requirement to implement orderly land administration. In this case, it means that the position of the roya permit deed of mortgage rights made by a notary is a custom in notarial practice.Keywords: Certificate; Deed; Mortgage; Roya.